1997
DOI: 10.1104/pp.115.2.847
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Phosphoribosylpyrophosphate Synthetase from Rubber Tree Latex

Abstract: Phosphoribosylpyrophosphate synthetase (PRS; EC 2.7.6.1) from Hevea brasiliensis Müll. Arg. latex was located in the cytosol. After purification, its apparent molecular weight under nondenaturing conditions was estimated at 200,000 f 10,000; a single band at 57,000 f 3,000 was detected after sodium dodecyl sulfatepolyacrylamide gel electrophoresis. l h e enzyme seemed to be a homotetramer. Its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…For example the rat liver enzyme exists in an aggregate form composed of 34-kDa (PRSI and PRSII), 39-kDa (PAP39), and 41-kDa (PAP41) subunits in a ratio of 20:5:8:1 (55). In rubber tree latex the enzyme seems to be a tetramer (56), although the crystal structure of the Bacillus subtilis PRS has shown it to be hexameric (57) and in Salmonella typhimurium the smallest active form of PRS may be pentameric (58).…”
Section: Discussionmentioning
confidence: 99%
“…For example the rat liver enzyme exists in an aggregate form composed of 34-kDa (PRSI and PRSII), 39-kDa (PAP39), and 41-kDa (PAP41) subunits in a ratio of 20:5:8:1 (55). In rubber tree latex the enzyme seems to be a tetramer (56), although the crystal structure of the Bacillus subtilis PRS has shown it to be hexameric (57) and in Salmonella typhimurium the smallest active form of PRS may be pentameric (58).…”
Section: Discussionmentioning
confidence: 99%
“…ATP functioned as a diphosphoryl donor, whereas neither GTP, CTP, nor UTP functioned as a diphosphoryl donor. Apparent K m values for ATP and ribose 5-phosphate were determined to be 0.2 M and 40 M, respectively (131). As before, the data should be reevaluated with the current knowledge of the multiple forms of PRPP synthases.…”
Section: Class II Prpp Synthasesmentioning
confidence: 99%
“…In a previous study, PRS preparations had been purified from rubber tree latex. Biochemical analysis revealed that Mg 2+ and P affected the activity of this latex PRS; and it used only ATP as the diphosphate group donor [ 18 ]. Based on the biochemical characteristics of this latex PRS and classification of PRS family proteins, it is safe to deduce that this latex PRS belongs to Class I PRS.…”
Section: Discussionmentioning
confidence: 99%
“…Energy availability, mainly constituted with the total content of adenine nucleotide, is a major factor affecting NR regeneration between two tappings [ 14 ]; while PRPP is a precursor to synthesize adenine nucleotide [ 1 ]. In earlier research, PRS preparations have been purified from rubber tree latex, which depend on Mg 2+ and P for activity, and used only ATP as the diphosphate group donor [ 18 ]. However, so far, no PRS genes have been cloned, let alone studied for their biological functions in rubber tree.…”
Section: Introductionmentioning
confidence: 99%